Impacts of nitrogen and phosphorus additions on the abundance and community structure of ammonia oxidizers and denitrifying bacteria in Chinese fir plantations. (December 2016) - Tang, Yuqian; Zhang, Xinyu; Li, Dandan; Wang, Huimin; Chen, Fusheng; Fu, Xiaoli; Fang, Xiangmin; Sun, Xiaomin; Yu, Guirui
Abstract: Nitrogen (N) cycling in forest ecosystems has been extensively studied over the past decade. However, even with this concentrated research effort, we still do not have a comprehensive understanding of how N-cycling microbial communities in subtropical plantations respond to N and phosphorus (P) additions. We designed an on-going fertilization experiment in which varying amounts of N or/and P were added to forest soil so that the effects of N and P applications on the abundances and community structures of nitrifying and denitrifying microbes in Chinese fir plantations in subtropical China could be explored using quantitative real time PCR ( q PCR) and high-throughput sequencing methods. The results showed that most N-cycle functional genes responded differently to N or/and P additions depending on the type and amount of nutrients added. Ammonia oxidizing archaea (AOA) were more abundant and active than ammonia oxidizing bacteria (AOB) in all treatments. While the abundances of nirK and nirS decreased under the high N applications, the abundances of narG increased. With the exception of AOB amoA and nirS, the abundances of all the functional genes were strongly and positively correlated with the concentrations of soil available P (AP) and negatively correlated with the ratio of available N to AP, which suggested that P had an important influence on the abundances of N-cycling microbes in these forest ecosystems. Shifts in communities of both AOA and nirK -type bacteria were driven by combined application of N and P, with group I.1a-associated and Rhizobiales as the most relatively abundant groups, respectively. Highlights: We examined the impacts of long-term N and P additions on N-cycle functional genes. AOA were more active in ammonia oxidation in the acidic forests than AOB. Low N had no impacts, while high N had various impacts, on N-cycle gene numbers. The abundances of AOA and most denitrifiers increased under P additions. The communities of AOA and nirK denitrifiers changed to adapt to N and P additions.